The Paper Industry in Its Relation to Conservation and the Tariff - Hess, Roscoe R. (Quarterly Journal of Economics, 1911)
I. Requirements for success: cheap spruce and cheap water power, 652. — Peculiarity of market for news paper, 654. — II. Combination in the industry, 656. — Business policy of the "trust, " 657. — III. The Tariff, 660. — Prohibition of exports of wood from Canadian provinces, 662. — Provisions of the Act of 1909, 664. — Importation of the pulps, 664. — The Conference Committee's insertion of a significant phrase, 665. — Importance of freight charges on pulp wood, 667. — Labor conditions in Canada and the United States, 671. — IV. Conservation, 673. — Methods of cutting timber, 674. — Analysis of causes leading to devastation, 675. — V. Conclusions as to the Tariff, 678.— American mills owning favorably situated woodland receive a rent, 679. — Probability of gradual extermination of inefficient and disadvantageously located mills, 681.